Controlling shareholders and fiduciary duties in common law Asia - Lim, E (2019)
This thesis is the first monograph to provide a critical and comparative examination of the question of why, when, by whom, and how fiduciary duties should be imposed on controlling shareholders in the listed companies in the four common law jurisdictions in Asia (Singapore, Hong Kong, Malaysia and India) as well as how those duties can be enforced. Because different ownership structures (i.e. dispersed versus concentrated) give rise to different corporate governance problems (i.e. separation of ownership and control versus extractions of private benefits of control), the question is whether the four Asian jurisdictions should depart from the current UK legal position (on which their laws are based)—shareholders do not owe fiduciary duties to the company—and impose such duties on the controlling shareholders. This thesis provides an affirmative answer and seeks to make three contributions. First, this thesis calls into question a long-standing, fundamental legal principle that shareholders unlike directors, should not owe fiduciary duties to the company as they can vote as they please and they are not agents. Second, this thesis deepens the existing analysis of the strategies that have been used to address extractions of private benefits of control by controlling shareholders by demonstrating that they are not only deficient, but they also fail to regulate other types of conflicts of interest which can give rise to tunneling. Finally, this thesis advances the debate on a central and fundamental concept in corporate law and governance—the interests of the company—from a normative, legal and empirical perspective by showing that corporate interest need not be equated with shareholders’ or stakeholders’ interests, but could refer to the long-term value and viability of the company.